Factors affecting the choice of dermatology as a specialty by medical students: Data from 28 KSA medical schools - Al-Mohaimeed, Danah M.; Aldera, Reema M.; Albdaya, Norah A.; Albusair, Moath K.; Shadid, Asem M.; Bukhari, Abrar E.; ALOmair, Ibrahim A. (International Journal of Health Sciences, 2022)
Objectives: Choosing a future career path is a very important decision for undergraduate medical students. Determining the factors that affect specialty choices is essential to attaining a balanced distribution. Dermatology is known to be one of the most appealing and highly competitive specialties. The aim of this study was to determine the factors influencing the choice of dermatology as a future career by medical students. Materials and Methods: A cross-sectional study was carried out in 28 medical schools throughout Saudi Arabia. The questionnaire was prepared following a literature search of relevant studies and was distributed electronically to medical students and interns. The self-administered questionnaire included sociodemographic data, interest in dermatology as a future career, and factors that may affect specialty choices. Results: The study included 1087 participants. Sixty percent were female, and 39% were male. Approximately half of the participants considered dermatology as their preferred specialty. We found that 53.6% of females were more interested in dermatology. Students who were exposed to dermatology in both pre-clinical and clinical years showed greater interest. Personal interest, lifestyle/flexible work schedule, and private sector opportunities were the most captivating factors. Personal interest and high competition in dermatology residency program matching were the main factors among students who did not consider dermatology as a future career choice. Conclusions: Several factors are influencing medical students when choosing dermatology as their future specialty; the lifestyle/flexible work schedule and personal interest were the most attractive factors. Recognizing these factors could be a useful tool that may lead mentors and residency training program directors to reach a balanced distribution of doctors in the various specialties.